Critical Success Factors For Iso 9000 Certification In The Malaysian Manufacturing Industry - Mohd Hussin, Rosminah (2003)
This study examines the critical success factors (CSFs) for ISO 9000 certification in the Malaysian manufacturing industry. A postal survey is used as research methodology. A newly designed set of questionnaire based on the identified CSFs has been sent to 600 randomly selected manufacturing companies in Malaysia. The results from an 1 1 % responses or 66 companies indicate that management commitment is the most important critical factor, followed by teamwork, employee involvement, communication, understanding of organization's quality system, training, understanding of ISO 9000 standards, institutionalizing the ISO 9000 quality concept and ISO 9000 project planning. Recommendations are made for future use, based on the five most popular CSFs that companies need to undertake in developing a successful strategy for ISO 9000 certification. Suggestions for future work include: investigation on how to maintain the ISO 9000 certification, and on how to convert the existing system of ISO 9000: 1994 to the new ISO 9000:2000.